The administration of UltraMimi Kids® UHT milk by PT. Ultrajaya Milk Industry increased body weight and did not increase estrogen hormone level in female albino rat (Rattus norvegicus) Wistar strain - Sabella; Wimpie Pangkahila; Anak Agung Ayu Ngurah Susraini (Neurologico Spinale Medico Chirurgico, 2021)
Background: This study aimed to prove that administration of UltraMimi Kids® UHT milk by PT. Ultrajaya Milk Industry increased body weight and estrogen levels in female albino rat (Rattus norvegicus) Wistar strain. Methods: This research was a true experimental with randomized pretest-posttest control group design. The research subjects were 18-female-albino-rats aged 21-days, weight 25-28 grams, divided into 2-groups: control group which was given standard food and sugar solution (0.36 grams of sugar dissolved in 1 ml aquadest), and intervention group which was given standard food and UltraMimi Kids® UHT milk 1 ml for the first 14-days and upgraded to 2 ml for the rest 14-days, given three times a day for 28-days. The rats body weight and estrogen levels were measured using Tanita-KD-192-digital-scales and ELISA method. Results: The control group had an increased body weight (26.2±1.2-66.1±5.94 grams; p<0,001), but there was no change in estrogen levels (38.59±11.19-44.59±5.42 ng/L; p=0.217). Whereas, the intervention group had an increased body weight (25.77±0.83-85.33±10.24 grams; p=0.008), but there was no change in estrogen levels (39.91±3.73-42.66±2.24 ng/L; p=0.066). After 28-days of intervention (posttest), it was found that the mean of body weight in the intervention group was higher than the control group (p<0.001), there was no significant difference in estrogen levels (p=0.339) and food intake from the remaining feed in both groups (0.51±0.81-0.36±0.55 grams; p=0.823). Conclusion: The administration of UltraMimi Kids® UHT milk by PT. Ultrajaya Milk Industry increased body weight and did not increase estrogen hormone level in female albino rat (Rattus norvegicus) Wistar strain.